Tanggapan Planlet Vanili yang Diradiasi dengan Sinar Gamma dan Keragaannya Setelah Diinokulasi dengan Jamur Fusarium oxysporum f.sp. vanillae - Woerjono Mangoendidjojo; Bambang Hadisutrisno; Alfi Inayati (Universitas Gadjah Mada, 2000)
Vanilla is one of spice crops and important to world commerce. Indonesia is one of producing and exporting countries for decades. Recently, the planted area tends to decrease due to several factors. One of them is fusarium wilt caused by Fusarium oxysporum fsp. vanillae. The disease ranked among the most devastating disease attacking vanilla plants. The most effective method controlling fusarium wilt is the use of resistant varieties. The study aimed to know responses of vanilla plantlets irradiated by Gamma rays at several doses (0-4 krad). Five months after irradiation, the survival mutant plantlets were inoculated with suspension of the F. oxysporum fsp. vanillae to evaluate their resistance. Data of first concern taken were survival plantlets; number of leave, root, and sucker initiation; and infection intensity. The results indicated that higher the doses, decreased the survival plantlets. The applied doses performed significantly differences on the number of leave, root, and suckerinitiation. The untreated plantlets showed better responses as compared to those treated. Evaluation on their resistance after inoculation indicated that the survival plantlets irradiated at 3 and 1 krad showed lower infection intensity, eventhough variation within a treatment was observed. Evaluation on the individual plantlet basis seemed to be more helpful in order to identify mutant plantlets with better resistance.